Dampak Rasio Pencampuran Bahan Bakar Diesel Terhadap Opasitas Asap Knalpot Mitsubishi L300 Tahun 2013 - Markus Wandani; Suprapto Suprapto; Henry Iskandar; Nur Basuki; Jubaidah Jubaidah (CV. IRA PUBLISHING, 2026)
High exhaust gas opacity in conventional Diesel vehicles, such as the 2013 Mitsubishi L300 with its conventional injection system, remains a significant environmental challenge. This study aims to analyze the impact of blending three Diesel fuel types—Biosolar, Dexlite, and Pertamina Dex—on exhaust opacity levels. Conducted at the Motor Vehicle Testing Unit in Medan, the research employed an experimental method using a Smoke Opacity Meter to measure smoke opacity at various fuel mixture ratios. Data were subsequently analyzed using ANOVA to identify significant differences between treatments. The results demonstrate that fuel blending significantly influences opacity values. Notably, the combination of Pertamina Dex and Dexlite yielded the lowest opacity levels, achieving an average reduction of over 30% compared to pure Biosolar. This improvement is attributed to higher cetane numbers and lower sulfur content, which facilitate more complete combustion. The study concludes that fuel blending is a practical strategy for mitigating emissions in conventional Diesel engines, supporting the development of eco-friendly fuels and sustainable transportation policies in Indonesia.